Beyond the ivory tower : international relations theory and the issue of policy relevance - Lepgold, Joseph; Nincic, Miroslav (New York : Columbia University Press, 2001)
The gap between academics and practitioners in international relations has widened in recent years, according to the authors of this book. Globalization, ethnic conflict, and ecological threats have created a new set of issues that challenge policymakers, and cutting-edge scholarship can contribute a great deal to the diagnosis and handling of potentially explosive situations.
The Theory-Practice Gap in International Relations -- Types of Knowledge and Their Practical Uses -- How Knowledge Is Acquired and Used -- Scholarship and Relevance: Is There a Tradeoff? -- The Inter-Democratic Peace-Theoretical Foundations and Policy Implication -- International Institutions and International Cooperation: Theoretical Foundations and Policy Implications -- Useful Knowledge: Value, Promise, and Limitations.
Includes bibliographical references (pages 187-213) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
In English.
Keywords: International relations; Diplomacy; International relations -- Philosophy; Relations internationales; Diplomatie; Relations internationales -- Philosophie; international relations; diplomacy; POLITICAL SCIENCE -- Globalization; POLITICAL SCIENCE -- International Relations -- General; Diplomacy; International relations; International relations -- Philosophy; Internationale betrekkingen; Theorie; Relevantie; 89.70 international relations: general; Internationale Politik; Diplomatie; International relations; Diplomacy; International relations -- Philosophy; Electronic books